Systemic Lupus Erythematosus and Thyroid Autoimmunity - Ferrari, Silvia Martina; Elia, Giusy; Virili, Camilla; Centanni, Marco; Antonelli, Alessandro; Fallahi, Poupak (Frontiers in Endocrinology, 2017)
Most of the studies present in the literature show a high prevalence, and incidence, of new cases of hypothyroidism and autoimmune thyroiditis (AT) in systemic lupus erythematosus (SLE) patients, overall in female gender. A limited number of cases of Graves’ disease (GD) have been also reported in SLE patients, in agreement with the higher prevalence of thyroid autoimmunity. It has been also demonstrated that a Th1 predominance is associated with AT in SLE patients. Furthermore a higher prevalence of papillary thyroid cancer has been recently reported in SLE, in particular in the presence of thyroid autoimmunity. However studies in larger number of SLE patients are needed to confirm findings about thyroid cancer. On the whole, data from literature strongly suggest that female SLE patients, with a high risk (a normal but at the higher limit thyroid-stimulating hormone value, positive anti-thyroid peroxidase antibodies, a hypoechoic pattern and small thyroid) should undergo periodic thyroid function follow-up, and approriate treatments when needed. A careful thyroid monitoring would be opportune during the follow-up of these patients.